Overexpressed PTOV1 associates with tumorigenesis and progression of esophageal squamous cell carcinoma - Rong Li; Ai-min Leng; Xiao-ming Liu; Ting-zi Hu; Lin-fang Zhang; Ming Li; Xiao-xia Jiang; Yan-wu Zhou; Can-xia Xu (Tumor Biology)
PTOV1 has been demonstrated to play an extensive role in many types of cancers. This study takes the first step to clarify the potential relationship between esophageal squamous cell carcinoma and PTOV1 expression and highlight the link between PTOV1 and the tumorigenesis, progression, and prognosis of esophageal squamous cell carcinoma. PTOV1 expression was detected by quantitative reverse transcription polymerase chain reaction and western blotting or immunohistochemical staining in esophageal squamous cell carcinoma cell lines, esophageal squamous cell carcinoma tissues, and its paired adjacent non-cancerous tissues. Moreover, we have analyzed the relationship between PTOV1 expression and clinicopathological features of esophageal squamous cell carcinoma. Survival analysis and Cox regression analysis were used to assess its prognostic significance. We found that PTOV1 expression was significantly higher in the esophageal squamous cell carcinoma cell lines and tissues at messenger RNA level (p < 0.001) and protein level (p < 0.001). Gender, tumor size, or differentiation was tightly associated with the PTOV1 expression. Lymph node involvement (p < 0.001) and TNM stage (p < 0.001) promoted a high PTOV1 expression. A prognostic significance of PTOV1 was also found by Log-rank method, and the overexpression of PTOV1 was related to a shorter OS and DFS. Multiple Cox regression analysis indicated overexpressed PTOV1 as an independent indicator for adverse prognosis. In conclusion, this study takes the lead to demonstrate that the overexpressed PTOV1 plays a vital role in the tumorigenesis and progression of esophageal squamous cell carcinoma, and it is potentially a valuable prognostic predicator and new chemotherapeutic target for esophageal squamous cell carcinoma.